The Implementation of Customary Court Within the Framework of Law Number 21 of 2001 Concerning Special Autonomy of the Province of Papua: A Study on Adat People of Kampong Waena, the District of Heram, Jayapura City - Rohman, Baitur; Kamil, Hutrin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
The Adat (customary) community in the province of Papua is of a diverse culture that respects and maintains Adat law. Under Law Number 21 of 2001 concerning Special Autonomy in the Province of Papua, an Adat community is defined as a group of native people of Papua who, since their birth, have been living in a particular territory, bound to, and compliant with a particular Adat law with solidarity upheld by the members of the community. This research seeks to analyse the legal tenets of the Adat court that the people of Waena have to abide by, how criminal offences are settled under an Adat court of Waena, and the impacts of the implementation of special autonomy in the Adat community of Waena within the scope of Adat law. This research employed an empirical-legal method, supported by primary and secondary data. Data were collected from in-depth interviews, observation, and documentation. The research results reveal that the locals of Waena uphold the Adat law passed from their ancestors, while also abiding by the state’s law as the general law (unification). The special autonomy in place in the community of Papua under Law Number 21 of 2001 reinforces the existence of Adat law and the role of an Adat court in resolving both private and criminal cases faced by the native people of Waena. The judiciary structure of the Adat community concerned consists of Ondofolo/ondoafi as the Chief Judge/chief of deliberation and koshelo in Kampong Waena as the members. Three pillars serve to govern the life of the people of Adat institution, churches, and the government of Kampong.